The Effect of Participative Leadership Style and Work Discipline on Employee Performance in Sosorgadong Subdistrict, Central Tapanuli Regency - Simanjuntak, Rido Permana (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the effect of Participative Leadership Style and Work Discipline on Employee Performance at the Government of Kecamatan Sosorgadong. This research employed a quantitative approach using a survey method. The population consisted of all employees at the Sosorgadong Subdistrict Office, with a total sample of 52 respondents determined using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 27. The results indicate that all research instruments are valid and reliable and have met the classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The regression equation obtained is Y = 39.880 – 0.269X1 + 0.209X2. Partially, Participative Leadership Style has a significance value of 0.061 (>0.05), and Work Discipline has a significance value of 0.108 (>0.05), indicating that both variables do not have a significant effect on Employee Performance. Simultaneously, the F-test shows a significance value of 0.106 (>0.05), meaning that both variables together do not significantly affect Employee Performance. The coefficient of determination (R²) is 0.087, which indicates that only 8.7% of Employee Performance variation can be explained by Participative Leadership Style and Work Discipline, while the remaining 91.3% is influenced by other factors outside the model.